Representations of Identity and Power in Leila S. Chudori's Novel Pulang - Zulfa, Mukminati; Asrofah, Asrofah; Asnawi, Asnawi (UIR Press, 2025)
This study aims to examine the representation of resistance in Leila S. Chudori's novel Pulang using Norman Fairclough's Critical Discourse Analysis (CDA) approach. The focus of the study is on how the narrative and discursive practices in the novel represent resistance to state hegemony, particularly in the context of the political and cultural identity of the Indonesian diaspora community after the events of 1965. Data was obtained through the identification of relevant quotations and analyzed based on Fairclough's three dimensions of CDA: text, discursive practices, and social practices. The results of the study show that resistance in Pulang is manifested not through physical action, but through symbolic narratives, discourse criticism, and claims to alternative histories. The characters in the novel reconstruct their identities through personal recognition, cultural heritage, and efforts to preserve collective memory outside the official state narrative. The allegory of Ekalaya's story reflects a form of symbolic resistance to authority; the critical questions of the younger generation reflect the desacralization of the state's narrative; and spaces such as the Tanah Air Restaurant function as sites of cultural resistance that construct counter-memories and identities. Overall, Pulang represents a transformative discourse that challenges dominant power and opens space for individual and collective agency in shaping history and identity. This research contributes to expanding understanding of literature as a medium of discursive resistance, and highlights the role of language and narrative in articulating diaspora identity and historical trauma in critical and transformative ways.